Understanding Redox Homeostasis and Its Role in Cancer - Dawane, Jayshree Shriram (JCDR Research and Publications (P) Limited, 2012)
When a cell is damaged or altered without repair to its system, it usually dies. But if such damaged or unrepaired cells do not die and proliferate with uncontrolled growth; a mass of cancer cells develop. Cancer has a complex aetiology with multiple risk factors that involve the interplay between genetic and environmental influences. The redox dysregulation originates from metabolic alterations and it is dependent on mitogenic and survival signalling through reactive oxygen species. There is a delicate balance between the production and the destruction of reactive species; for this, we need to understand the role of redox homeostasis in cancer. So, the specific vulnerability of the malignant cells can be selectively targeted. This article will outline the redox homeostasis and the relationship between the disturbances in it and cancer.